Aisyiyah Dan Pemberdayaan Perempuan Dalam Upaya Kesetaraan Gender - Nur Kholisatun; Fika Ratna Pratiwi; Moh. Nurhakim (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The differences between men and women often lead to gender inequality, which results in stereotypes against women. The issue of the position and role of women remains an interesting subject to study. Since the establishment of Muhammadiyah, KH. Ahmad Dahlan has paid great attention to the development of women. Under the guidance of KH. Ahmad Dahlan and Nyai Walidah (the wife of KH. Ahmad Dahlan), they founded an organization named “Aisyiyah” to elevate the status and dignity of Muslim women. This research is descriptive with qualitative data support that is inductive in nature, which means the research starts from specific realities and then abstracts them into general conclusions. The data sources required for this research are found in both primary and secondary books. The results of the research show that Aisyiyah also played a role in the formation of Indonesian women's organizations by advocating for equal rights between men and women. Gender equality, as understood by Aisyiyah, is based on abilities rather than gender or physical appearance. One of Aisyiyah's concrete actions in empowering women and promoting equal rights is in the field of education. During the Dutch colonial period, women were able to receive the same level of education as men. The role of women in accessing various spaces has been realized by Aisyiyah through tangible programs that continue to this day.